Applied theatre : bewilderment and beyond - Thompson, James (Oxford ; New York : P. Lang, 2012)
Applied Theatre: Bewilderment and Beyond explores the practice of theatre in communities and social institutions with marginalised groups. It shifts between contexts and countries to examine different ways that theatre has been applied to a wide range of social issues. Theatre projects in Brazil, Burkina Faso, Sri Lanka and the United Kingdom are analysed to argue for a complex and questioning view of the practice. Initiatives in prisons, developing countries, war situations and participatory research projects become the sites to interrogate the claims that applied theatre can be a theatre for social change.
Many practitioners and researchers have witnessed powerful applied theatre projects but nonetheless struggled to articulate the reasons for the projects’ success. This book uses the questions inspired by that perplexity to create a case for applied theatre as a major area of contemporary theatre practice.
Bibliografija: str. [181]-187. - Kazalo
Keywords: Community theater; Theater and society; Drama in education; Prison theater; Theater and older people; Children's theater; kazalište u zajednici; kazalište i društvo; drama i obrazovanje; primjenjeno kazalište